Pengaruh Positifitas Leukosit Esterase dan Nitrit Urine Terhadap Nilai Neutrophil Lymphocyte Ratio (NLR) pada Pasien Infeksi Saluran Kemih - Kholisha, Citra Dian; Zaetun, Siti; Jiwantoro, Yudha Anggit; Resnhaleksmana, Ersandhi (Jurnal Kesehatan Andalas, 2023)
Urinary tract infection (UTI) characterized by positivity of leukocyte esterase and nitrite can affect the Neutrophil Lymphocyte Ratio (NLR) value as a reflection of the degree of infection and inflammation by pathogenic microorganisms. Objective: To analyzed the effect of positivity leukocyte esterase and nitrite urine on NLR values in UTI patients. Methods: This study used an observational analytic method with a cross-sectional approach. UTI patients will be subjected to urinalysis and complete blood cell examination. The data obtained will be subjected to the Pearson correlation and linear regression tests. Results: This study used 36 samples of UTI patients with an abnormal number of positive leukocyte esterase samples in 36 samples (100%), positive urine nitrite in 20 samples (55,6%), and abnormal NLR values >3,5 are 27 samples (75%) with a mean of 10,21. Conclusion: There is a significant influence and relationship between the positivity of leukocyte esterase and urine nitrite on NLR value in UTI patients with a simultaneous value of 45,1% and p 0,000.Keywords: Â UTI, leukocyte esterase, urine nitric, NLR